Detection of fastidious bacteria in cardiac valves in cases of blood culture negative endocarditis. Issue 3 (1st March 2001) - Bruneval, P; Choucair, J; Paraf, F; Casalta, J-P; Raoult, D; Scherchen, F; Mainardi, J-L
Abstract : The diagnosis of blood culture negative endocarditis is still a problem. Fastidious bacteria such as bartonella and coxiella are responsible for cases of blood culture negative endocarditis, the identification of which is mainly based on serological and DNA studies only available in specialised centres. Therefore, a routine technique is needed in surgical pathology laboratories to detect these bacteria in cardiac valve tissue sections. This report describes a staining technique, the Giménez stain, feasible and sensitive in detecting bartonella and coxiella in two cases of blood culture negative endocarditis.